The Relationship Between Backward Strike Flexibility and Arm Strength and Inward Throwing Ability in Football - Awaluddin, Awaluddin; Latuheru, Ricardo Valentino (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to find out the relationship between the flexibility of the strikeback and the strength of the arm with the ability to throw the ball inward in a football game. This research is a type of correlational descriptive research. The population of this study is all students of SMPN 19 Makassar with a research sample of 80 male students who are selected by proportional random sampling. The data analysis techniques used are simple and multiple correlation analysis techniques. Based on the results of data analysis, this study concludes that: There is a significant relationship between the flexibility of the backward strike and the ability to throw the ball inward in a football game, (ro = 0.771 > rt = 0.220); There was a significant relationship between arm strength and inward throwing ability in football games, (ro = 0.540 > rt = 0.195); There was a significant relationship between the flexibly of the strike back and the strength of the arm with the ability to throw the ball inward in the game of football (Ro = 0.772 > Rt = 0.195).